SENSITIVITY OF PIGMENT CONTENT OF BANANA AND ORCHID TISSUE CULTURE EXPOSED TO EXTREMELY LOW FREQUENCY ELECTROMAGNETIC FIEL - Riry Prihatini; Norihan Mohamad Saleh (Indonesian Agency for Agricultural Research and Development, 2016)
Natural exposure of extremely low frequency electromagnetic field (ELF-EMF) occurs in the environment and acts as one of the abiotic factors that affect the growth and development of organisms. This study was conducted to determine the effect of ELF-EMF on the tissue cultured banana and slipper orchid chlorophyll content as one of the indicators in measuring plant photosynthetic capacity. Four days old banana (Musa sp. cv. Berangan) corm and seven days old slipper orchid (Paphiopedilum rothschildianum) cultures were exposed to 6 and 12 mT ELF-EMF generated by controllable ELF-EMF built up machine for 0.5, 1, 2 and 4 hours. After exposure, the banana and orchid cultures were incubated at 25° C for 8 and 16 weeks, respectively. The results showed that the ELF-EMF exposure had different effects on banana and slipper orchid cultures though both plant species belong to monocotyledon. The highest increase in chlorophyll content on banana was resulted by the high intensity and long duration of ELF-EMF exposure (12 mT for 4 hours), whereas on slipper orchid the modest and short duration of ELF-EMF exposure produced the most excessive chlorophyll content. Different ELF-EMF exposures (12 mT for 4 hours and 6 mT for 30 minutes) had potential to be applied on each plant to improve in vitro plant (banana and slipper orchid, respectively) growth. The increased chlorophyll and carotene/xanthophyll content on banana indicated that the banana was more tolerant to ELF-EMF exposure compared to slipper orchid.